All-solid-state lithium-sulfur battery and preparation method thereof

By designing a coating layer and a solid electrolyte layer with excellent electronic and ionic conductivity in the all-solid-state lithium-sulfur battery, the conductivity and stability issues were solved, and an all-solid-state lithium-sulfur battery with high energy density and high safety was realized.

CN120955190APending Publication Date: 2025-11-14SHENZHEN YITONG ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511063506.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-30
Publication Date
2025-11-14

AI Technical Summary

Technical Problem

All-solid-state lithium-sulfur batteries suffer from poor ionic and electronic conductivity due to the fact that both sulfur and lithium disulfide are insulators. The redox kinetics between solid-phase sulfur and solid-phase lithium sulfide are slow, and the sulfur-lithium disulfide reaction leads to large volume changes, resulting in poor electrode stability and easy pulverization, which affects battery performance and safety.

Method used

A composite positive electrode-electrolyte structure is formed by using a first coating layer with excellent electronic conductivity and a second coating layer with excellent ionic conductivity, combined with a solid electrolyte layer, to improve conductivity and electrolytic conductivity, and then forming an all-solid-state battery by hot pressing.

Benefits of technology

It improves the charge/discharge rate, cycle stability, and safety of all-solid-state lithium-sulfur batteries, making them suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120955190A_ABST
    Figure CN120955190A_ABST
Patent Text Reader

Abstract

The invention provides an all-solid-state lithium-sulfur battery. The all-solid-state lithium-sulfur battery comprises a first coating layer, a second coating layer, a solid electrolyte layer and a lithium negative electrode, the first coating layer is a positive electrode layer with excellent electronic conductivity and comprises a sulfur positive electrode active material, a conductive agent, sulfide electrolyte and a binder, and the content of the conductive agent is relatively high; the second coating layer is a composite positive electrode-electrolyte layer with excellent ionic conductivity, and comprises a sulfur positive electrode active material, a conductive agent, a sulfide electrolyte, a lithium salt and a binder; the solid electrolyte layer is composed of a polymer electrolyte, a lithium salt and an additive. According to the all-solid-state lithium-sulfur battery and the preparation method thereof provided by the invention, the electronic conductivity and the ionic conductivity of a sulfur electrode are improved, meanwhile, the problem of poor contact between a positive electrode interface and electrolyte is solved, a reaction energy barrier in a sulfur charge-discharge process is greatly reduced, and the charge-discharge rate of the all-solid-state lithium-sulfur battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, specifically to an all-solid-state lithium-sulfur battery and its preparation method. Background Technology

[0002] As the new energy power battery field places increasingly higher demands on battery technology for safety and high energy density, traditional liquid batteries are increasingly unable to meet consumer needs, especially in terms of safety performance. Therefore, the development of high-energy-density and high-safety solid-state batteries has become the trend of future industry development.

[0003] As a promising next-generation high-performance battery, the all-solid-state lithium-sulfur battery has attracted increasing attention from researchers due to its high energy density (2600 Wh / kg) and high safety. Lithium-sulfur batteries use sulfur / lithium disulfide as the positive electrode and lithium as the negative electrode. Elemental sulfur has a theoretical specific capacity as high as 1675 mAh / g and is inexpensive and abundant. However, the development of all-solid-state lithium-sulfur batteries faces many challenges: sulfur and lithium disulfide are both sulfur insulators with poor ionic and electronic conductivity; the redox kinetics between solid-phase sulfur and solid-phase lithium sulfide are slow; and the large volume change caused by the sulfur-lithium disulfide reaction leads to poor electrode stability and susceptibility to electrode pulverization. These factors pose challenges to the performance and safety of lithium-sulfur batteries, hindering their commercial application.

[0004] To address the aforementioned issues, it is necessary to develop an all-solid-state lithium-sulfur battery, its preparation method, and its applications. Summary of the Invention

[0005] The purpose of this invention is to provide an all-solid-state lithium-sulfur battery and its preparation method, which improves the charge-discharge rate, cycle stability and safety of the all-solid-state lithium-sulfur battery.

[0006] On one hand, this invention provides an all-solid-state lithium-sulfur battery, comprising a first coating layer, a second coating layer, a solid electrolyte layer, and a lithium anode; the first coating layer is a positive electrode layer with excellent electronic conductivity, comprising a sulfur positive electrode active material, a conductive agent, a sulfide electrolyte, and a binder, wherein the conductive agent content is relatively high; the second coating layer is a composite positive electrode-electrolyte layer with excellent ionic conductivity, comprising a sulfur positive electrode active material, a conductive agent, a sulfide electrolyte, a lithium salt, and a binder.

[0007] Furthermore, the weight ratio of sulfur positive electrode active material, conductive agent, sulfide electrolyte and binder in the first coating layer is 60-85:10-25:1-5:4-10; the thickness of the first coating layer is 50-300 μm.

[0008] Furthermore, the weight ratio of sulfur positive electrode active material, conductive agent, sulfide electrolyte, lithium salt and binder in the second coating layer is 50-80:5-10:10-25:1-5:4-10; the thickness of the second coating layer is 50-200 μm.

[0009] Furthermore, the sulfur positive electrode active material includes any one or a combination of at least two of elemental sulfur, sulfur / carbon composite material, sulfur / conductive polymer composite material, and metal-organic framework (MOFs) / sulfur composite material, preferably sulfur / carbon composite material.

[0010] Furthermore, the conductive agent includes any one or a combination of at least two of Ketjen black, conductive carbon black SP, graphene, carbon fiber, and carbon nanotubes.

[0011] Furthermore, the sulfide electrolyte includes Li 5.5 PS 4.5 Cl 1.5 Li6PS5Cl, Li7P3S 11 Li7P2S8I, Li3PS4 and Li 10 GeP2S 12 Any one of them.

[0012] Furthermore, the adhesive includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene rubber, and polyethylene oxide.

[0013] Furthermore, the lithium salt is lithium bis(trifluoromethane)sulfonylimide (LITFSI) or lithium perchlorate (LiClO4).

[0014] Further, the solid electrolyte layer comprises a polymer electrolyte, a lithium salt, and additives in a weight ratio of 60-85:5-20:10-20; the polymer electrolyte comprises any one of PEO and PVDF-HFP; the lithium salt is lithium bis(trifluoromethane)sulfonylimide (LITFSI) or lithium perchlorate (LiClO4); the additives comprise at least one of β-alumina, titanium dioxide, lithium nitride, Li3PS4, LLZO, and LiGa(SeO3)2; and the thickness of the solid electrolyte layer is 5-50 μm.

[0015] On the other hand, the present invention also provides a method for preparing an all-solid-state lithium-sulfur battery, the steps of which include: the first coating layer is coated on the surface of an aluminum current collector by means of slurry, the second coating layer is coated on the surface of the first coating layer by means of slurry roller coating or spraying, the resulting electrode is a positive electrode-solid electrolyte composite, the lithium negative electrode is a lithium copper composite strip, the positive electrode composite and the negative electrode are cut into specific shapes, stacked in sequence with positive electrode-solid electrolyte-negative electrode as units, and hot-pressed together at a pressure of 500 MPa and a heating temperature of 80°C to form a bare cell, and after encapsulation, a solid-state battery can be obtained.

[0016] The beneficial effects of this invention are as follows:

[0017] This invention provides an all-solid-state lithium-sulfur battery and its preparation method. By coating an aluminum current collector with a first coating layer exhibiting good electronic conductivity and a second coating layer exhibiting good ionic conductivity, and then forming a solid electrolyte layer in situ on the surface of the second coating layer, the electronic and ionic conductivity of the sulfur electrode is improved. Simultaneously, the problem of poor contact between the positive electrode interface and the electrolyte is solved, significantly reducing the reaction energy barrier during sulfur charge-discharge processes and increasing the charge-discharge rate of the all-solid-state lithium-sulfur battery, enabling it to operate at room temperature and atmospheric pressure. The composite solid electrolyte membrane, composed of the second coating layer and the solid polymer electrolyte layer, effectively improves the lithium-ion conductivity and the mechanical strength of the electrolyte membrane, protects the sulfide electrolyte in the second coating layer from contact with air, and solves the problem of side reactions between the sulfide electrolyte and the lithium negative electrode, effectively improving the cycle stability and safety of the all-solid-state lithium-sulfur battery. Furthermore, the preparation method used in this invention can be fully automated using existing equipment, making it suitable for large-scale industrial production. Attached Figure Description

[0018] Figure 1 This is a schematic diagram of the internal structure of an all-solid-state lithium-sulfur battery.

[0019] Wherein, 1-first coating layer, 2-second coating layer, 3-solid electrolyte layer, 4-lithium anode. Detailed Implementation

[0020] The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0021] Example 1

[0022] like Figure 1As shown in Embodiment 1, an all-solid-state lithium-sulfur battery includes a first coating layer 1, a second coating layer 2, a solid electrolyte layer 3, and a lithium anode 4. The first coating layer 1 includes a sulfur positive electrode active material, a conductive agent, a sulfide electrolyte, and a binder. The second coating layer 2 includes a sulfur positive electrode active material, a conductive agent, a sulfide electrolyte, a lithium salt, and a binder.

[0023] The preparation method of all-solid-state lithium-sulfur batteries is as follows:

[0024] (1) Preparation of lithium-sulfur cathode sheet:

[0025] In a drying chamber, sulfur / carbon composite materials, graphene, carbon nanotubes, and Li are... 5.5 PS 4.5 Cl 1.5 The binder PVDF is mixed evenly in a solvent N-methylpyrrolidone (NMP) at a mass ratio of 80:6:7:3:4 to obtain the first coating layer positive electrode slurry.

[0026] Sulfur / carbon composite material, conductive carbon black SP, Li 5.5 PS 4.5 Cl 1.5 LITFSI and binder PVDF are mixed evenly in N-methylpyrrolidone (NMP) solvent at a mass ratio of 70:5:20:1:4 to obtain the second coating layer positive electrode slurry.

[0027] The first coating layer positive electrode slurry and the second coating layer positive electrode slurry are sequentially coated onto the aluminum foil of the aluminum current collector. The coating thicknesses of the first coating layer and the second coating layer are 100μm and 100μm, respectively. After drying in a coating machine oven and pressing with a 50T pressure roller, the positive electrode sheet is obtained.

[0028] (2) Preparation of solid electrolyte layer:

[0029] In a drying chamber, PEO, LITFSI, and Li3PS4 are dispersed in acetonitrile at a mass ratio of 80:5:15 to obtain an electrolyte slurry. The slurry is then coated onto the surface of the positive electrode sheet. After drying, a solid electrolyte layer is formed on the surface of the second coating layer of the positive electrode. The thickness of the solid electrolyte layer is 15 μm. After slitting and cutting, a positive electrode-solid electrolyte positive electrode composite is obtained.

[0030] (3) Preparation of negative electrode sheet:

[0031] In a drying room or under a protective dry atmosphere, a 50μm thick lithium metal strip is hot-pressed and laminated with a carbon-coated copper foil to obtain a lithium-copper composite strip. The thickness of the lithium metal layer on one side after lamination is 25μm. The lithium metal layer on one side of the lithium-copper composite strip is nitrided, and the strip is then slit and cut to obtain a negative electrode sheet.

[0032] (4) Fabrication and testing of pouch-type all-solid-state batteries:

[0033] In a drying chamber, the positive electrode composite of the positive electrode and the negative electrode sheet of the above-mentioned positive electrode-solid electrolyte are stacked in sequence. The internal structure of the cell is shown in the schematic diagram below. Figure 1 As shown, the cells are hot-pressed at 80°C under a pressure of 500 MPa and stacked to form a soft-pack all-solid-state battery with a designed capacity of 10 Ah.

[0034] The test was conducted at room temperature using a clamp with a pressure of 5MPa. The test method was as follows: (1) Cyclic durability test: The battery was discharged to 1.5V at 0.3C and then charged to 3.0V in the first cycle. The long cycle test of 0.3C discharge / 0.3C charge was carried out, with a voltage cutoff range of 1.8V to 2.8V.

[0035] (2) High-rate discharge test: Charge the battery to 3.0V at a rate of 0.3C, let it stand for 1 hour, and then discharge it to 1.5V at a rate of 3C to obtain the discharge capacity at a high rate.

[0036] (3) Needle penetration safety test: After the battery is charged to 3.0V at a rate of 0.3C, a steel needle with a diameter of 3mm and a taper of 45° is used to penetrate the center of the cell vertically at a speed of 0.1mm / s for 1 hour. The cell is observed to see if it catches fire or explodes. The number of cell samples is 3pcs.

[0037] The test results show that (1) at a 0.3C rate, the battery's initial discharge capacity was 1100mAh / g, and after 100 cycles of 0.3C discharge / 0.3C charging, the battery capacity retention rate was 96%, demonstrating excellent reversible capacity performance and cycle stability. (2) at a 3C rate, the cell's discharge capacity retention rate was 85% (relative to the 0.3C rate discharge capacity), demonstrating excellent rate performance. (3) The needle penetration safety test results show that none of the 3 cells caught fire or exploded, with a 100% pass rate, demonstrating excellent safety performance.

[0038] Example 2

[0039] This embodiment is basically the same as Embodiment 1, except that the first coating layer and the second coating layer of the sulfur cathode contain sulfide electrolytes Li. 5.5 PS 4.5 Cl 1.5 Replace with Li3PS4.

[0040] Example 3

[0041] This embodiment is basically the same as Embodiment 1, except that the first coating layer and the second coating layer of the sulfur cathode contain sulfide electrolytes Li. 5.5 PS 4.5Cl 1.5 Replace with Li 10 GeP2S 12 .

[0042] Example 4

[0043] This embodiment is basically the same as Embodiment 1, except that the PVDF binder in the first and second coating layers of the sulfur cathode is replaced with PTFE.

[0044] Example 5

[0045] This embodiment is basically the same as Embodiment 1, except that the lithium salt LITFSI in the second coating layer and solid electrolyte layer of the sulfur cathode is replaced with LiClO4.

[0046] Example 6

[0047] This embodiment is basically the same as Embodiment 1, except that the polymer electrolyte PEO in the solid electrolyte layer is replaced with PVDF-HFP.

[0048] Example 7

[0049] This embodiment is basically the same as Embodiment 1, except that the additive Li3PS4 in the solid electrolyte layer is replaced with lithium nitride.

[0050] Example 8

[0051] This embodiment is basically the same as Embodiment 1, except that the additive Li3PS4 in the solid electrolyte layer is replaced with LLZO.

[0052] Example 9

[0053] This embodiment is basically the same as Embodiment 1, except that the coating thicknesses of the first coating layer and the second coating layer of the sulfur cathode are 50 μm and 200 μm, respectively.

[0054] Example 10

[0055] This embodiment is basically the same as Embodiment 1, except that the coating thicknesses of the first coating layer and the second coating layer of the sulfur cathode are 300 μm and 50 μm, respectively.

[0056] Example 11

[0057] This embodiment is basically the same as Embodiment 1, except that the thickness of the solid electrolyte layer is 5 μm.

[0058] Example 12

[0059] This embodiment is basically the same as Embodiment 1, except that the thickness of the solid electrolyte layer is 50 μm.

[0060] Comparative Example 1

[0061] This embodiment is basically the same as Embodiment 1, except that: the surface of the second coating layer of the positive electrode is not coated with a solid electrolyte layer, the positive electrode and the negative electrode are separated by a PE separator with the same thickness of 15μm as the solid electrolyte, and the electrolyte 1MLiTFSI / DOL:DME(1:1)+1%LiNO3 is injected and assembled into a soft-pack liquid battery using the same process.

[0062] Comparative Example 2

[0063] This embodiment is basically the same as Embodiment 1, except that: the sulfur cathode does not have a second coating layer, the wet film thickness of the first coating layer is 200μm, and everything else is the same. The same process is used to stack and assemble them into a soft-pack all-solid-state battery.

[0064] Comparative Example 3

[0065] This embodiment is basically the same as Embodiment 1, except that: the sulfur cathode does not have a first coating layer, and the wet film thickness of the second coating layer is 200μm. Everything else is the same, and the same process is used to stack and assemble them into a soft-pack all-solid-state battery.

[0066] Batteries for each embodiment and comparative example were prepared according to the above method, and various performance parameters were measured. The results are shown in the table below.

[0067] Table 1

[0068]

[0069]

[0070] From the data in the table above, we can see that:

[0071] The all-solid-state lithium-sulfur batteries of the various embodiments of this application not only have better cycle performance and rate performance, but also have better energy density and safety performance than liquid lithium-sulfur batteries, and have excellent overall performance.

[0072] Comparing Examples 1 and 2-3, it can be seen that the choice of sulfide electrolyte in the first and second coating layers of the sulfur cathode has a certain impact on the battery cycle performance and rate performance. Sulfide Li, with higher room temperature ionic conductivity, is particularly effective. 5.5 PS 4.5 Cl 1.5 and Li 10 GeP2S 12 It has better performance than Li3PS4.

[0073] Comparing Examples 1 and 4, it can be seen that the type of binder in the first and second coating layers of the sulfur cathode has little impact on the battery performance.

[0074] Comparing Examples 1 and 5, it can be seen that the type of lithium salt in the second coating layer and the solid electrolyte layer of the sulfur cathode has a certain impact on the battery performance. The lithium salt LITFSI exhibits better battery performance than LiClO4, which may be related to the fact that the lithium salt provides better lithium-ion conductivity and better interfacial reaction with the positive and negative electrodes.

[0075] Comparing Examples 1 and 6, it can be seen that the type of polymer electrolyte in the solid electrolyte layer has a certain impact on the battery performance. PEO has better room temperature lithium-ion conductivity than PVDF-HFP, thus the battery has better cycle performance and rate performance.

[0076] Comparing Examples 1 and 7-8, it can be seen that the type of additive in the solid electrolyte layer affects the performance of the battery. Li3PS4 exhibits better cycle stability and rate performance than lithium nitride and LLZO, mainly due to the room temperature ionic conductivity of the additive and its good contact reaction with the positive electrode interface.

[0077] Comparing Examples 1 and 9-10, it can be seen that the thickness of the first and second coating layers of the sulfur cathode affects the performance of the battery. If the thickness of the first or second coating layer is too thin, it will affect the electronic conductivity or ionic conductivity of the sulfur cathode. Only when the thickness is moderate and the distribution is uniform, and the electronic and ionic conductivity of the sulfur cathode is good, can the cycle performance and rate performance of the battery be better achieved.

[0078] Comparing Examples 1 and 11-12, it is evident that the thickness of the solid electrolyte layer affects the electrochemical and safety performance of the battery. A thin (5 μm) solid electrolyte film is beneficial for improving the battery's rate performance, but it also increases the risk of short circuits between the positive and negative electrodes. A thick (50 μm) solid electrolyte film can reduce the risk of short circuits between the positive and negative electrodes, better ensuring battery safety, but it increases the lithium-ion transport distance, affecting the battery's cycle stability and rate performance. Therefore, an appropriate solid electrolyte thickness is a good guarantee for the battery's electrochemical and safety performance.

[0079] Comparing Example 1 and Comparative Example 1, it can be seen that the all-solid-state lithium-sulfur battery has better cycle performance and safety performance than the liquid lithium-sulfur battery. This is because the liquid lithium-sulfur battery has the problem of the shuttle effect of intermediate polysulfide products in the liquid electrolyte, and the polysulfides react and deposit on the surface of the negative electrode. The all-solid-state lithium-sulfur battery does not have this problem, so its cycle performance is better. Because the electrolyte of the liquid lithium-sulfur battery is flammable, it is very easy for the battery to undergo thermal runaway due to short circuit and combustion in the nail penetration test. Therefore, its safety performance is not as good as that of the all-solid-state lithium-sulfur battery.

[0080] Comparing Example 1 and Comparative Examples 2-3, it can be seen that the dual-layer design of the first and second coating layers of the sulfur cathode simultaneously considers the electronic and ionic conductivity of the sulfur cathode. The excellent electronic conductivity of the first coating layer near the aluminum current collector ensures that electrons are quickly conducted from the cathode to the aluminum current collector, reducing electronic impedance; while the excellent ionic conductivity of the second coating layer near the solid electrolyte membrane ensures that lithium ions can be quickly conducted between the electrolyte membrane and the cathode, reducing ionic impedance. Therefore, compared with the single-layer electrode designs of Comparative Examples 2 and 3, the battery of Example 1 has better cycle stability and rate performance.

[0081] Finally, it should be noted that the above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention; those skilled in the art should understand that modifications or equivalent substitutions can still be made to the present invention; and all technical solutions and improvements that do not depart from the spirit and scope of the present invention should be covered within the scope of the claims of the present invention.

Claims

1. A fully solid-state lithium-sulfur battery, characterized in that, It includes a first coating layer (1), a second coating layer (2), a solid electrolyte layer (3), and a lithium anode (4); the first coating layer (1) includes a sulfur positive electrode active material, a conductive agent, a sulfide electrolyte, and a binder; the second coating layer (2) includes a sulfur positive electrode active material, a conductive agent, a sulfide electrolyte, a lithium salt, and a binder.

2. The all-solid-state lithium-sulfur battery according to claim 1, characterized in that, The weight ratio of sulfur positive electrode active material, conductive agent, sulfide electrolyte and binder in the first coating layer (1) is 60-85:10-25:1-5:4-10; the thickness of the first coating layer (1) is 50-300 μm.

3. The all-solid-state lithium-sulfur battery according to claim 1, characterized in that, The weight ratio of sulfur positive electrode active material, conductive agent, sulfide electrolyte, lithium salt and binder in the second coating layer (2) is 50-80:5-10:10-25:1-5:4-10; the thickness of the second coating layer (2) is 50-200 μm.

4. A solid-state lithium-sulfur battery according to any one of claims 1 to 3, characterized in that, The sulfur positive electrode active material includes any one or a combination of at least two of elemental sulfur, sulfur / carbon composite materials, sulfur / conductive polymer composite materials, and metal-organic framework / sulfur composite materials.

5. A solid-state lithium-sulfur battery according to any one of claims 1 to 3, characterized in that, The conductive agent includes any one or a combination of at least two of Ketjen black, conductive carbon black SP, graphene, carbon fiber, and carbon nanotubes.

6. A solid-state lithium-sulfur battery according to any one of claims 1 to 3, characterized in that, The sulfide electrolyte includes Li 5.5 PS 4.5 Cl 1.5 Li6PS5Cl, Li7P3S 11 Li7P2S8I, Li3PS4 and Li 10 GeP2S 12 Any one of them.

7. A solid-state lithium-sulfur battery according to any one of claims 1 to 3, characterized in that, The adhesive includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene rubber, and polyethylene oxide.

8. A solid-state lithium-sulfur battery according to claim 1 or 3, characterized in that, The lithium salt is lithium bis(trifluoromethane)sulfonylimide or lithium perchlorate.

9. A solid-state lithium-sulfur battery according to claim 1, characterized in that, The solid electrolyte layer (3) comprises a polymer electrolyte, a lithium salt, and additives in a weight ratio of 60-85:5-20:10-20; the polymer electrolyte comprises any one of PEO and PVDF-HFP; the lithium salt is lithium bis(trifluoromethane)sulfonylimide or lithium perchlorate; the additives comprise at least one of β-alumina, titanium dioxide, lithium nitride, Li3PS4, LLZO, and LiGa(SeO3)2; and the thickness of the solid electrolyte layer (3) is 5-50 μm.

10. A method for preparing an all-solid-state lithium-sulfur battery according to any one of claims 1-9, characterized in that, The first coating layer (1) is coated on the surface of the aluminum current collector by slurry, and the second coating layer (2) is coated on the surface of the first coating layer (1) by slurry. The solid electrolyte layer (3) is formed on the surface of the second coating layer (2) by slurry roller coating or spraying. The resulting electrode is a double-layer positive electrode-solid electrolyte positive electrode composite. The lithium negative electrode (4) is a lithium copper composite strip. The positive electrode composite and the negative electrode are cut and stacked in sequence as positive electrode-solid electrolyte-negative electrode units. They are bonded together by 500 MPa isostatic pressure to form a bare cell. After encapsulation, a solid battery can be obtained.